EFFECTS OF PHYSICAL EXERCISE ON THE FUNCTIONAL AUTONOMY OF ELDERLYI (Fiep Bulletin - online, 2016)
The aging process is natural and irreversible, bringing diseases of aging and bodily losses. However, it is possible to prove that exercise can be an excellent choice to reduce the causes of this process and to age with more health. In this sense, the objective of this research was to survey existing research in order to understand what the effects caused by exercise that contribute to the functional autonomy of the elderly. The methodology used to develop the research was qualitative type of literature, from a survey of journal articles and academic books. The results were that exercise promotes well-being and optimizes the quality of life, independence / functional autonomy, slows the diseases of aging, prevents diseases like diabetes and hypertension, and also promotes the increase in maximal oxygen consumption. Given the results, the final considerations of this research are that the exercise by causing positive effects on the practitioner, helping to optimize the functional independence of older people.
Keywords: Physical Exercise; Functional Autonomy; Elderly.